2007
DOI: 10.1016/j.molcel.2007.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitination of FANCD2 Is Required for DNA Crosslink Repair

Abstract: SummaryMonoubiquitination of FANCD2 and PCNA promotes DNA repair. It causes chromatin accumulation of FANCD2 and facilitates PCNA's recruitment of translesion polymerases to stalled replication. USP1, a protease that removes monoubiquitin from FANCD2 and PCNA, was thought to reverse the DNA damage response of these substrates. We disrupted USP1 in chicken cells to dissect its role in a stable genetic system. USP1 ablation increases FANCD2 and PCNA monoubiquitination but unexpectedly results in DNA crosslinker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
181
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(193 citation statements)
references
References 28 publications
(56 reference statements)
10
181
0
2
Order By: Relevance
“…De-ubiquitination of the Fanconi Anemia D2 protein, FANCD2, by the USP1 DUB represents a second example in which DUB activity is necessary to terminate DNA damage-inducible ubiquitination events (30). Failure to either ubiquitinate FANCD2 or to de-ubiquitinate FANCD2-Ub confers sensitivity to DNA cross-linking agents (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De-ubiquitination of the Fanconi Anemia D2 protein, FANCD2, by the USP1 DUB represents a second example in which DUB activity is necessary to terminate DNA damage-inducible ubiquitination events (30). Failure to either ubiquitinate FANCD2 or to de-ubiquitinate FANCD2-Ub confers sensitivity to DNA cross-linking agents (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The PP2A phosphatase dephosphorylates ␥H2AX, and indeed, PP2A deficiency renders cells IR-sensitive (33). Additionally, sustained levels of mono-ubiquitinated FANCD2 in USP1-null cells confers reduced viability after DNA damage (31). Thus, opposing activation and termination responses on ␥H2AX and other proteins involved in DNA repair appear to be crucial to maintain viability after DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…1G; Nijman et al 2005;Cohn et al 2007). Of note, genetic disruption of murine Usp1 results in a phenotype similar to FA, and both Usp1 and Uaf1 knockout chicken DT40 cells exhibit hypersensitivity to DNA cross-linking agents (Oestergaard et al 2007;Kim et al 2009;Murai et al 2011). Therefore, USP1-dependent deubiquitination constitutes another critical repair step in the completion of DNA ICL repair.…”
Section: The Fanconi Anemia (Fa) Pathwaymentioning
confidence: 99%
“…11 USP1 has been identified as a key regulator in the DNA repair processes, mainly in the Fanconi anemia pathway and Translesion DNA synthesis by regulating ubiquitination status of FANCD2 and PCNA, 12,13 Mono-ubiquitinated FANCD2 and PCNA serve as a platform to recruit DNA repair proteins to DNA damage sites, [14][15][16] and USP-induced deubiquitination of FANCD2 and PCNA is crucial for the correct function of DNA repair pathway. 17,18 Indeed, Usp1 gene deletion in mice 18 and USP1 inhibition by small molecules displayed chemosensitizing effects against DNA damaging agents, [19][20][21] indicating that USP1 is required for an efficient DNA repair activity. Besides DNA repair-related function, recent study reveals that increased level of USP1 is found in human osteosarcoma cell lines.…”
Section: Introductionmentioning
confidence: 99%